Prove the identity: sin³x+cosx³=(sinx+cosx)(1-sinxcosx)?
回答 (1)
I'm guessing you mean cos³x, not cosx³.
Also, the equation is not displaying correctly because it is too long. You need to insert a few spaces to break it up:
sin³x+cos³x = (sinx+cosx) (1-sinxcosx)
Remember how to factor the sum of cubes:
a³+b³ = (a+b) (a²-ab+b²)
sin³x + cos³x = (sinx + cosx) (sin²x - sinxcosx + cos²x)
Since sin²x + cos²x = 1,
sin³x + cos³x = (sinx + cosx) (1 - sinxcosx)
收錄日期: 2021-04-21 21:54:26
原文連結 [永久失效]:
https://hk.answers.yahoo.com/question/index?qid=20160915094436AA3pF7H
檢視 Wayback Machine 備份